The Case for Real Food...Reprinted by permission of Harper, an imprint of HarperCollins Publishers. - Lustig, Robert H. (Integrative & Complementary Therapies, 2025)
The article focuses on the distinction between "Real Food" and processed food, emphasizing the health implications of food processing and the importance of understanding what happens to food before it reaches consumers. It argues that much of what is produced by industrial agriculture can be considered toxic due to processing methods, which strip food of its beneficial properties and introduce harmful substances. The author advocates for a shift towards Real Food, which protects liver health and supports gut health, as a means to combat chronic diseases, particularly in children. The article also outlines practical shopping strategies to help consumers make healthier choices and calls for a cultural shift in how society views food and nutrition.